A snapshot of the global policies and practices of medicine use reviews by community pharmacist in the management of chronic diseases: a narrative review - Mubarak, Naeem; Zin, Che Suraya (2019)
INTRODUCTION Significant differences exist in how community pharmacist (CP) is being utilized around the globe. OBJECTIVE To explore various policies and practices of medicine use review (MUR) by CP in chronic diseases and, its impact and way forward for low- and middle- income countries (L&MIC) METHOD Narrative review, using key words, such as ″medicine use review″, ″medication therapy management″ and ″community pharmacy″ in databases such as PubMed, and Scopus from 2004-2017 to include reviews, overviews, systematic reviews and meta-analyses on the policy, practice and impact of MUR. Studies on attitude or perception were excluded. RESULTS MUR opened an avenue of ongoing collaboration between CP and general practitioners. In terms of policies and practices, the situation in high-income countries was quite encouraging where on an average ″type-II″ medicine use review was widely in practice and has improved clinical, humanistic and economic outcomes in chronic disease patients. The high-income countries witnessed gradual yet cautious adoption of these services through effective policy shift. However, in L&MIC, a paucity of effective policies was noted. Nevertheless, an emergent recognition of the potential of CPs to contribute in healthcare delivery was evident. CONCLUSION Promising impact of CPs involvement in the management of chronic diseases was evident in high income countries, however, the situation in L&MIC, which bear an overwhelming share of the global burden of chronic diseases, remains skimpy. Authors believe that way forward to a paradigm shift in any country must involve consensus building methods to bring relevant stakeholders on the same page.